Ex Vivo Area-Metric Analysis of Root Canal Obturation Using Cold and Warm Gutta-Percha - Katarzyna Olczak; Leszek Klimek; Halina Pawlicka (Advances in Materials Science and Engineering)
Purpose. To evaluate the percentage content of gutta-percha, sealer, and voids in a filled canal area following three different filling techniques, using microphotographs and Nis Elements® software. Material and Methods. After completing chemomechanical preparation, the teeth (n=48) were randomly divided into three groups (n=16) and filled by either cold lateral condensation (CLC group), the continuous wave technique (EOU group), and the ProTaper® thermoplasticized obturator (PT group). The roots were then sectioned horizontally 2.5, 6.5 and 8.5 mm from the tooth apical foramen. The surface areas of the sealer, voids, and gutta-percha (PGFA percentage of gutta-percha-filled area) were calculated and the results subjected to statistical analysis (Kruskal-Wallis test). Results. The percentage of gutta-percha (PGFA) was lower in the apical third of the canal for the CLC and EOU groups than the PT group. In the middle and the coronal third of the canal, the PGFA value was higher after using thermal techniques (EOU and PT) than cold lateral condensation (CLC). The presence of voids was comparable in the fillings performed using warm and cold gutta-percha obturation at all levels. Conclusion. Although thermal methods of root canal obturation allow higher PGFA values to be obtained than cold lateral condensation, the content of voids is comparable.